2014
DOI: 10.36733/jsp.v4i2.446
|View full text |Cite
|
Sign up to set email alerts
|

Improving Speaking Skill and Developing Character of the Students Through Collaboration of Think-Pair-Share and the Concept of Tri Kaya Parisudha

Abstract: ABSTRAKKeterampilan berbicara merupakan salah satu keterampilan yang harus selalu dilatih agar mereka dapat berkomunikasi dengan baik.Di samping itu, karakter juga merupakan salah satu hal yang sangat penting karena orang yang sukses bukan hanya karena hard skill tetapi juga soft skill.Penelitian ini ditujukan untuk mengatasi permasalahan yang dihadapi oleh mahasiswa semester tiga Program Studi Pendidikan Bahasa Inggris yaitu keterampilan berbicara dan karakter.Penelitian dilaksanakan dalam beberapa siklus pen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
12
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 0 publications
2
12
1
Order By: Relevance
“…LMS can be said to be a learning management prepared for students and lecturers in learning through software. The LMS software that can be used include: ACS, Blackboard, CarPoint, Moodle, Canvas, Google Classroom, and so on (Jöns and Hoyler, 2013, Yuliana, 2013, Budiarta and Krismayani, 2014. The results of a preliminary study of the types of LMS found that goggle classroom is a multiplatform application that can be used by users.…”
mentioning
confidence: 99%
“…LMS can be said to be a learning management prepared for students and lecturers in learning through software. The LMS software that can be used include: ACS, Blackboard, CarPoint, Moodle, Canvas, Google Classroom, and so on (Jöns and Hoyler, 2013, Yuliana, 2013, Budiarta and Krismayani, 2014. The results of a preliminary study of the types of LMS found that goggle classroom is a multiplatform application that can be used by users.…”
mentioning
confidence: 99%
“…Thus, it effectively raises the need for student literacy, especially for those who are willing to struggle, the need for learning to take on a number of complex activities (Manis et al, 2004). So, reading is the process for someone in analyzing and interpreting the meaning contained in the source of information or text (Henard andRoseveare, 2012, Budiarta andKrismayani, 2014). Thus, it can be understood that reading is a person's process of understanding the meaning of a text (Lindsey et al, 2003, Henard andRoseveare, 2012).…”
Section: Reading Englishmentioning
confidence: 99%
“…So, students in this action research learn to read well in order to understand the meaning of the text. The ability to read can be used for daily life both for the benefit of the educational process, work, and social life (Moussu and Llurda, 2008, Budiarta and Krismayani, 2014,Antony et al, 2015.…”
Section: Reading Englishmentioning
confidence: 99%
See 1 more Smart Citation
“…As an act of receptive language, reading can be matched by listening. However, reading has at least one main characteristic that distinguishes it from listening (Budiarta andKrismayani, 2014, Syakur, 2018b). This characteristic is that reading is solitary, not social, in the sense that the dependency of the listener on the speaker does not exist with the reader on the script writer (Páez and Rinaldi, 2006).…”
Section: Introductionmentioning
confidence: 99%